Collection, cryopreservation, storage, and revitalization of transgenic mouse embryos - Schwab, Anna; Schenkel, Johannes (Cold Spring Harbor protocols, 2008)
INTRODUCTION - Transgenic mice possess enormous scientific potential. However, the need to maintain breeding stocks to prevent the loss of unique mutants (particularly if they are not in current use for experiments) is a major challenge. Cryopreservation of spermatozoa or preimplantation embryos is a valuable tool to address this issue, with cryopreservation of embryos in the two- to eight-cell stage being the most common method. Cryopreserved samples can be stored indefinitely in liquid nitrogen, and cryopreserved embryos can be shipped easily. Colonies of a transgenic line need not be maintained if a sufficient stock of embryos has been cryopreserved. After revitalizing preserved samples, embryo transfer must be used to re-establish the line. However, considerable effort is often needed to obtain a sufficient number of embryos. This protocol describes the methods necessary to collect and cryopreserve eight-cell embryos and to handle cryopreserved samples, as well as subsequent procedures needed to revitalize and re-derive transgenic lines.